Pengujian Automation Testing pada Website E-Learning - Fauzi, Muhammad Alvy Eka; Cahyadi, Septian (Jurnal Informatika Kesatuan, 2024)
This study aims to identify and resolve complaints of IBIK LMS users who are used as a means of teaching and learning activities during the COVID-19 pandemic. The survey was conducted on 42.2% of respondents from Information Technology students and IBIK lecturers. Using the Software Testing Life Cycle (STLC), the author developed a test plan by dividing the IBIK LMS into modules based on the main functions and roles. Functional testing using the black box method was conducted to assess software performance. Test results were automated using automation testing to facilitate future testing and assist LMS developers. Errors in functionality and performance were found, although the fulfillment of user requirements was quite good (0.81). The bottleneck in automation testing was caused by the session login feature which thwarted the testing process. This research provides insight into improvements to the IBIK LMS and more effective testing strategies. Keyword: Information Technology, Software Testing Life Cycle, Automation Testing